##
**ALGEBRA FORMULAS**

**(a+b)**

^{2}

**= (a**

^{2}

**+b**

^{2}

**+2ab)**

**(a-b)**

^{2}

**= (a**

^{2}+

**b**

^{2}

**– 2ab)**

**(a+b)**

^{2}

**+ (a-b)**

^{2}

**= 2 (a**

^{2}

**+ b**

^{2}**)**

**(a+b)**

^{2}

**– (a-b)**

^{2}

**= 4ab**

**(a**

^{2}**-b**

^{2}**) = (a+b) (a-b)**

**(a+b)**

^{3}**= a**

^{3}

**+ b**

^{3}

**+ 3ab (a+b)**

**(a-b)**

^{3}

**= a**

^{3}

**– b**

^{3}

**-3ab (a-b)**

**(a**

^{3}**+b**

^{3}**) = (a+b) (a**

^{2}**-ab+b**

^{2}**)**

**(a**

^{3}**-b**

^{3}**) = (a-b) (a**

^{2}**+ab+b**

^{2}**)**

**Arithmetic progression (A.P)**

**Series a, a+d, a+2d, a+3d,…….**

**First term = a**

**Difference = d**

**Then**

**n**

**th**

**term T**

**n**

**= a + (n-1)d**

**sum of “n” term S**

**n**

**= n/2 – (2a + (n-1)d)**

**sum of n term S**

**n**

**= n/2 (a+L)**

**L = last term**

**Geometric progression (G.P)**

**a , ar, ar**

**2**

**,…….**

**First term = a**

**Difference = r**

**Then**

**n**

**th**

**term T**

**n**

**= ar**

^{n-1}

**sum of “n” terms S**

**n**

**= a(r**

^{n}

**– 1 )/ (r – 1)**

## 0 comments:

## Post a Comment